2023
DOI: 10.1038/s41467-023-40195-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 vaccination and previous infection on Omicron SARS-CoV-2 infection and relation with serology

Abstract: An increasing proportion of the population has acquired immunity through COVID-19 vaccination and previous SARS-CoV-2 infection, i.e., hybrid immunity, possibly affecting the risk of new infection. We aim to estimate the protective effect of previous infections and vaccinations on SARS-CoV-2 Omicron infection, using data from 43,257 adult participants in a prospective community-based cohort study in the Netherlands, collected between 10 January 2022 and 1 September 2022. Our results show that, for participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
3
14
1
Order By: Relevance
“…COVID-19 vaccines show waning vaccine effectiveness over time, as was previously also observed in the VASCO study (10), and in line with the observed waning of S-antibodies in this study. We also reported lower vaccine effectiveness among participants with medical risk conditions, but it was not obvious that the difference in VE between those with and without medical risks changed over time (10). This is in line with our finding that S-antibodies of those with and without medical risk do not wane at a different pace.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…COVID-19 vaccines show waning vaccine effectiveness over time, as was previously also observed in the VASCO study (10), and in line with the observed waning of S-antibodies in this study. We also reported lower vaccine effectiveness among participants with medical risk conditions, but it was not obvious that the difference in VE between those with and without medical risks changed over time (10). This is in line with our finding that S-antibodies of those with and without medical risk do not wane at a different pace.…”
Section: Discussionsupporting
confidence: 92%
“…We earlier showed a dose-response relationship between S-antibody GMC and protection against infection (10). COVID-19 vaccines show waning vaccine effectiveness over time, as was previously also observed in the VASCO study (10), and in line with the observed waning of S-antibodies in this study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations